Effect of salinity and density of Artemiasalina on magnesium and calcium impurities levelin salt production (Funded work) - MISRI GOZAN; SITI FAUZIYAH RAHMAN; HERMAWAN (International Journal of Pharma and Bio Sciences, 2017)
Salt is one of the versatile commodities that are used from the household to the chemical industry. The number of national salt production is still not sufficient so far, particularly those which is used for industrial needs. The quality of salt is determined by the concentration of NaCl. The concentration of NaCl in salt for consumption must be higher than 94% while salt for industrial use must contained NaCl higher than 98%. The residual components of salt are impurities, including magnesium and calcium. Artemia is organism that lives in sea water and has ability to intake magnesium and calcium in sea water for biological activity. This study is intended to determine the optimal density of Artemia salina and sea water salinity in decreasing concentration of magnesium and calcium in sea water to improve the quality of salt. Artemia salina cysts was hatched and reared to reach adult phase. Artemia was used in beaker glass for decreasing magnesium and calcium in sea water. The content of magnesium, calcium, chloride, and sulfate in sea water was analyzed. The result of this study showed that the reduction of ion content in sea water, e.g. magnesium, calcium, sulfate, and chloride content was slightly constant. The effect of salinity in decreasing concentration of magnesium and calcium was not shown as the alteration of salinity did not affect the reduction of magnesium and calcium significantly. The optimum salinity to decrease the concentration of magnesium and calcium is 6.8% while the optimum density of Artemia is 500 individuals per liter.